Recent advancements in the minimally invasive management of esophageal perforation, leaks, and fistulae. (4th March 2019) - Siddiqi, Shirin; Schraufnagel, Dean P.; Siddiqui, Hafiz Umair; Javorski, Michael J.; Mace, Adam; Elnaggar, Abdulrhman S.; Elgharably, Haytham; Vargo, Patrick R.; Steffen, Robert; Hasan, Saad M.; Raja, Siva
ABSTRACT: Introduction : Historically, the gold standard management of esophageal perforations, leaks, and fistulae has been traditional open surgery, but it is associated with significant morbidity and mortality. Minimally invasive approaches offer alternatives to surgery in treating hemodynamically stable patients with such defects. In this review article, we will discuss the recent advancements in the minimally invasive management of esophageal perforations, leaks, and fistulas. Areas covered : This review includes information from case reports, case series, and clinical trials on minimally invasive management of esophageal perforations, leaks, and fistulas. The focus is on the devices, outcomes, and application of the technology. Expert commentary : Minimally invasive treatment represents significant progress in the management of esophageal perforations, leaks, and fistulas. Based on current evidence, it seems safe and effective but it is evolving and more studies are needed to help draw definitive conclusions.